The effect of passive lower limb training on heart rate asymmetry. (31st January 2022) - Shi, Ping; Li, Anan; Wu, Liang; Yu, Hongliu
Abstract: Objective. Heart rate asymmetry (HRA) is an approach for quantitatively assessing the uneven distribution of heart rate accelerations and decelerations for sinus rhythm. We aimed to investigate whether automatic regulation led to HRA alternation during passive lower limb training. Approach. Thirty healthy participants were recruited in this study. The protocol included a baseline (Pre-E) and three passive lower limb training trials (E1, E2 and E3) with a randomized order. Several variance-based HRA variables were established. Heart rate variability (HRV) parameters, i.e. mean RR, SDNN, RMSSD, LF (n.u.), HF (n.u.) and VLF (ms 2 ), and HRA variables, i.e. SD1a, SD1d, SD2a, SD2d, SDNNa and SDNNd, were calculated by using 5 min RR time series, as well as the normalized HRA variables, i.e. C1a, C1d, C2a, C2d, Ca and Cd . Main results. Our results showed that the performance of HRA was distinguished. The normalized HRA was observed with significant changes in E1, E2 and E3 compared to Pre -E. Moreover, parts of non-normalized HRA variables correlated with HRV parameters, which indicated that HRA might benefit in assessing cardiovascular modulation in passive lower limb training. Significance. In summary, this study suggested that passive training led to significant HRA alternation and the application of HRA gave us the possibility for autonomic assessment.